Preliminary report on anaerobic culture at Mymensingh Medical College Hospital in Bangladesh - Ahmed, S; Hossain, MA; Musa, AK; Shamsuzzaman, AK; Mahmud, MC; Nahar, K; Paul, SK; Sumona, AA; Begum, Z; Zahan, NA; Huda, SN; Ahmed, MU; et al. (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):10-15. The abstract of this article is available on the PubMed website